STRATEGI GERAI INFORMASI DAN MEDIA DALAM MEMBANGUN CITRA POSITIF MELALUI DISEMINASI INFORMASI PUBLIK - Nila, Nila (Universitas Prof. Dr. Moestopo (Beragama), 2012)
Transparency of public information is the important thing in good govenrmment. To give transparency of public information about Indonesia education department, public relations made program that is âInformation and me-dia counterâ. Management function of public relations that reseach, planing, implemention, and evaluation the program. Public relations try to give excellent service information using many chanel such as : Email, phone, and face-to-face. This program is one of the strategy that public relations made for positif image of the government.